Effects of 4- Aminopyridine on Inflammatory Reactions in Experimental Models - SA Mirshafyei; V Molakazemiha; MM Amiri; A Salehinodeh; A Razavi; MR Khoramizadeh; R Gholamnejad (Tehran University of Medical Sciences, 2009)
Background And Aim : Nowadays, many inflammatory diseases such as rheumatoid arthritis (RA) and Multiple sclerosis (MS) and many other autoimmune inflammatory diseases has involved the people of different communities and cure for them so far has not been provided. Many waste irreparable these diseases caused by overexertion and chronic inflammatory cells and effects of destructive enzymes. Proteolysis like matrix Mtaloproteinazes (MMPs). Hence in this study was discussed effect of drug 4 - amino pyridine (4-AP) to Progress of inflammation in a experimental model of inflammatory response.Materials and Methods: In this study were used, 48 Out bred rat race, all female Sprague Dawely about 200-150 gr Weight and ages 6 to 8 weeks to induce inflammatory response experiment By bovine Serum albumin (BSA) + adjuvant complete Freund (CFA). Rats were in six groups of 8 each, including: Normal group, patient group, groups of Treatment-1,Treatment-2 , Prevention-1 and Prevention-2. drug 4-AP at different concentrations (400 and 800 micrograms) to groups of Treatment-1, 2 and Prevention-1, 2 rate (0 / 1 microliter) were injected and 48 to 72 hours after injection dosage reminder (only BSA) studied and were compared severity of inflammation.Results: 48 Rats that were studied, eight rats (66/16%), no inflammatory signs, histopathology and production of antibody anti-BSA did not show and this same group were normal. 8 rats (66/16%) clear signs of severe inflammation showed that were our patient group.32 rats (66/66%), showed less severe signs of inflammation than patients that were the same groups of Treatment-1, 2 and Prevention-1, 2 that they had been received different concentrations of 4-AP.Discussion and Conclusion: The difference in the severity of inflammation and diffuse infiltration of inflammatory cells in Evaluation clinical, radiology, histopathology and rate of antibody anti- BSA shows that the drug 4-AP reduces the severity of inflammation in the Groups receiving medication than normal and the patient group (p <0.05). Although statistical analysis showed 4-AP Has no effect on production rate of MMPs. The groups of rats had received high concentration the drug (Prevention2 and Treatment2) than groups that low concentration of the drug (Prevention-1 and Treatment-1) showed lower signs of inflammatory.